Association of air pollution with increased incidence of ventricular tachyarrhythmias recorded by implantable cardioverter defibrillators: Vulnerable patients to air pollution. (1st August 2017) - Kim, In-Soo; Sohn, Jungwoo; Lee, Seung-Jun; Park, Jin-Kyu; Uhm, Jae-Sun; Pak, Hui-Nam; Lee, Moon-Hyoung; Kim, Changsoo; Joung, Boyoung
Abstract: Background: This study investigated the acute effects of exposure to air pollution on ventricular tachyarrhythmias (VTAs) in an East Asian population. The association between air pollution and VTA has not yet been studied in an East Asian country affected by the Asian dust phenomenon, which worsens air quality. Methods: The study cohort consisted of 160patients with implantable cardioverter defibrillator (ICD) devices in the Seoul metropolitan area who were followed for 5.5 ± 3.8 years. We used ICD records of VTAs and matched these with hourly measurements of air pollutant concentrations and meteorological data. Fine particle mass and gaseous air pollution plus temperature and relative humidity were measured hourly during the study period. Results: During the study period, 1064 VTA events including 204 instances of ventricular fibrillation (VF) were observed. We found a statistically significant association between overall VTA events and SO2 (lag 24 h; OR 1.49, 95%CI 1.16–1.92, p = 0.002), PM10 (lag 2 h; OR 2.56, 95%CI 2.03–3.23, p < 0.001), NO2 (lag 24 h; OR 1.25, 95%CI 1.19–1.31, p < 0.001) and CO (lag 24 h; OR 1.05, 95%CI 1.02–1.08, p = 0.003). Sustained ventricular tachycardia or VF was also independently associated with SO2, PM10, NO2 and CO (all p < 0.01). Exposures to SO2, PM10, NO2, and CO (all p < 0.01) were significantly related to overall VTAs, especially in patients with structural heart disease (SHD). Conclusions: Associations between air pollution and VTA were observed in a metropolitan area of an East Asian country. Exposures to SO2, PM10, NO2, and CO were significantly associated with VTAs in ICD patients with SHD.